POTENSI BAHAYA ERGONOMI PADA PEKERJA HOME INDUSTRY KUN ART DI JALAN DANAU SINGKARAK MEDAN TAHUN 2013 - Nadya .; eka Lestari; Muhammad Makmur Sinaga (Lingkungan dan Kesehatan Kerja, 2013)
Ergonomic Potensial Hazard in Home Industry Kun Art Workers at Jalan Danau Singkarak Medan 2013. One of the potential hazards at home industry which is still very less attention is the ergonomics potential hazards, this is caused by a lack of knowledge on the workers. The purpose of this research is to know at the ergonomic potential hazards at work process that focuses on human-machine systems, work posture, work station layout and manual handling. This is a descriptive research, by observing work activities starting from the process of pattern making, pattern assembly, attachment of finishing materials and processes contained at "Home Industry Kun Art" Medan 2013. The research was conducted in July 2012 - March 2013 with a sample of seven workers and there was no difference potensial hazards effect of the sample. The results may lead to musculoskeletal disorders, cumulative trauma disorders and low backpain in the body of workers, especially in the arms, back and neck because vibration by the machine being used, work posture is wrong as sitting, standing and squatting in long periods of time, layout of the work area are irregular, and a wrong way to lift workers when lifting products. So that the workers should be advised to use leather gloves to avoid direct exposure to vibration, workers should perform stretching on the sidelines of the working time, the home owner should do the rearranging industry workplaces and workers to improve the way in order to avoid lifting the wrong way lift. Keyword : Ergonomics, Man Machine System, Work Posture, Layout, Manual Handling.